Material characterization of SiC and Al2O3–reinforced hybrid aluminum metal matrix composites on wear behavior. (7th June 2019) - AM, Rajesh; Kaleemulla, Mohamed; Doddamani, Saleemsab; KN, Bharath
In the present investigation, wear test is conducted on a pin-on-disc device at room temperature for both the age hardening and without age hardening conditions. Al7075 has been chosen as the matrix material. Hybrid aluminum metal matrix composites are produced utilizing stir casting route for enhancing the wear behavior and hardness number. The reinforcement used is silicon carbide with 5, 10, and 15 wt% and alumina as the reinforcement in 5, 10, and 15 wt%. In the aluminum matrix, microstructural characterization reveals homogeneous mixing of reinforcements. This investigation shows that the enhanced wear resistance is due to the increment weight fraction of reinforcement. By raising the sliding speeds, there is a reduction in the rate of wear and it reduces with increment in the sliding distance. With increasing weight fraction, there is decrement in the rate of wear of composites. In general, tribological property enhances because of the addition of the two reinforcements.